PENGARUH KUALITAS PELAYANAN, HARGA, DAN PROMOSI TERHADAP KEPUASAN PENGGUNA MAXIM DI KOTA PADANG - afif ulwan (Jurnal Teori dan Riset Administrasi Publik, 2023)
This researchx is motivated by the occurrence of several problems in ServiceAQuality, Price, and Promotion ofaMaxim User Satisfactionain Padang City which are seen in the parameters of the Study in Padang City, West Sumatra Province, whichxaims to determine the Effect of Service Quality, Price, and Promotion on User Satisfaction. Maxim in Padang City. This research is an associative researchxusingxquantitative descriptive analysis. The results of this research has showathatAServiceaQuality,aPricedand Promotion simultaneously havedaesignificantreffectdon Maxim user satisfactiontin Padang City, Servicerqualitythasta positive and significant effectyon Maxim user satisfaction in Padang City, Pricexhasxa positive and significant effect on Maxim userxsatisfaction in Padang City, and Promotionxhas a positive and significant effect on Maxim user satisfaction in Padang City.